Epigenetics of human T cells during the G0→G1 transition - Smith, Alexander E.; Chronis, Constantinos; Christodoulakis, Manolis; Orr, Stephen J.; Lea, Nicholas C.; Twine, Natalie A.; Bhinge, Akshay; Mufti, Ghulam J.; Thomas, N. Shaun B.

(untitled) (Genome Research, 2009)
We investigated functional epigenetic changes that occur in primary human T lymphocytes during entry into the cell cycle and mapped these at the single-nucleosome level by ChIP-chip on tiling arrays for chromosomes 1 and 6. We show that nucleosome loss and flanking active histone marks define active transcriptional start sites (TSSs). Moreover, these signatures are already set at many inducible genes in quiescent cells prior to cell stimulation. In contrast, there is a dearth of the inactive histone mark H3K9me3 at the TSS, and under-representation of H3K9me2 and H3K9me3 defines the body of active genes. At the DNA level, cytosine methylation (meC) is enriched for nucleosomes that remain at the TSS, whereas in general there is a dearth of meC at TSSs. Furthermore, a drop in meC also marks 3′ transcription termination, and a peak of meC occurs at stop codons. This mimics the 3′ nucleosomal distribution in yeast, which we show does not occur in human T cells.